2009
DOI: 10.1097/smj.0b013e3181aa5f5b
|View full text |Cite
|
Sign up to set email alerts
|

Health Insurance and the Development of Diabetic Complications

Abstract: Not having health insurance was a risk factor for developing diabetic complications in a group of predominantly Hispanic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Patients with diabetes having health insurance are more likely to have better glycemic control and lower rates of diabetic eye disease compared to those lacking health insurance. 16,49,50 Given the lower DR rate in the pharmacy cohort, it may be that screening in this setting will have lower yield than in outpatient clinics, an issue for further study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes having health insurance are more likely to have better glycemic control and lower rates of diabetic eye disease compared to those lacking health insurance. 16,49,50 Given the lower DR rate in the pharmacy cohort, it may be that screening in this setting will have lower yield than in outpatient clinics, an issue for further study.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 , 21 Indeed, patients with no health insurance or who are underinsured are more likely to experience diabetes-related complications and lower extremity amputations. 7 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy in LEA prevalence by geo- graphic area may also be partly attributable to regional differences in care and treatment. According to previous research with Medicare patients (35)(36)(37), the procedures for many types of surgery, including LEA in persons with diabetes, vary highly across geographic areas. A study at a teaching hospital in the Texas border area found that people with diabetes who had no insurance were twice as likely to suffer from limb amputations as those with some form of insurance (37).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research with Medicare patients (35)(36)(37), the procedures for many types of surgery, including LEA in persons with diabetes, vary highly across geographic areas. A study at a teaching hospital in the Texas border area found that people with diabetes who had no insurance were twice as likely to suffer from limb amputations as those with some form of insurance (37). These findings suggest that geographic variations in LEA prevalence may be explained by differences in population characteristics, insurance benefits, surgery capacity, and care and treatment styles.…”
Section: Discussionmentioning
confidence: 99%